The importance of Blood Flow Restriction Training (BFRT) in Physiotherapy: A Review of Literature - Abhishek Kumar Sandilya; Divya Kashyap; Arunmozhi; Meghna Wadhwa; Vishal Verma (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Blood Flow Restriction Treatment (BFRT) is a rehabilitation method that appears to generate improvements in hypertrophy comparable with heavy weightlifting. Despite its growing popularity, the extent to which BFRT has penetrated the physical therapy (PT) industry is unknown. The goal of this study was to evaluate PT's knowledge of and usage of BFRT in clinical settings. The objective of this study was to determine the significance of BFRT in different medical situations and evaluate its therapeutic effects from a physiotherapeutic perspective. PubMed, ResearchGate, Google Scholar, ScienceDirect, Advanced Google Scholar, and Elsevier were used as research databases to locate relevant literature reviews. Ten publications were selected based on predetermined inclusion criteria; these studies collectively provided evidence supporting the efficacy of BFRT in the field of physiotherapy. There appear to be gaps between PT's awareness of BFRT and its implementation in practice, although most of these professionals are willing to give it a shot. Most BFRT practitioners believe that the therapy is successful and plan to use it in the future. More education and training could improve the PT's capacity to use BFRT, as well as possibly improve their long-term clinical outcomes.